Effects of in-store information quality and store credibility on consumer engagement in green retailing. (March 2023) - Kumar, Prashant; Utkarsh,
Abstract: Literature has reported that store-level information is crucial in determining consumer engagement with green stores. This study examines the effects of in-store (green) information quality on consumer engagement behaviours and mediating effects of store credibility. Moreover, the study reveals whether consumer passion for the environment moderates the effect of in-store (green) information quality on store credibility. Statistical analyses of useable data from 763 respondents examined the relationships. Credibility emerged as a key mechanism to enhance the effects of information quality on consumer engagement. Thus, this study extends theoretical discussions on information quality, consumer passion, and consumer engagement for green retailing.